في سلسلة أسعار النفط الخام (برنت) خلال الثورات العربية 2011-2015 ( Volatility ) بناء نموذج لتفسير سلوك التقلبات - عادل محمد الشركسي (Scientific Journal of University of Benghazi, 2019)
This paper aims to build a statistical model using the GARCH family that is able to explain the behavior and the movement of fluctuations (Volatility) for the daily prices of crude oil (Brent) during the period from January 2011 to December 2015, and the GARCH family models were used because they are able to take into account returns and volatility, which is a measure of risk during trading hours, simultaneously. The results of this study showed that the best model that explains these fluctuations is the TGARCH model (1,1,1) with a positive leverage effect, which indicates that the relationship between returns and volatilities is an inverse relationship, meaning that bad news have more effects on oil prices than good news.